FACTORS AFFECTING TURNOVER INTENTIONS MEDIATED BY JOB SATISFACTION IN PRIVATE BANKS IN THE JABODETABEK AREA - Kevin, Kevin Ondo Hasudungan; Dita Oki Berliyanti; Medina, B. Medina Nilasari (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2025)
Turnover intention is one of the strategic challenges in human resource management, especially in the banking industry operating in the Greater Jakarta area. High employee turnover can disrupt the operational stability of a company. This study aims to analyze the influence of Work-Life Balance and Work Personal Life Enhancement on Turnover Intention, with Job Satisfaction as a mediating variable. This study employs a quantitative approach through the distribution of questionnaires to 124 private bank employees in the Jabodetabek region. The data analysis technique used is Structural Equation Modeling based on the AMOS software. The results of the study indicate that Work-Life Balance and Work Personal Life Enhancement have a significant negative influence on Turnover Intention, as well as a significant positive influence on Job Satisfaction. Additionally, Job Satisfaction was found to significantly mediate the relationship between the two variables and Turnover Intention. These findings emphasize the importance of creating a balanced work environment that supports employees' personal life enrichment to enhance job satisfaction and reduce employees' intention to leave the organization. Companies need to design policies that not only focus on work targets but also on employees' overall psychological well-being.